PENYULUHAN KESEHATAN REMAJA TENTANG ANEMIA DI SMA NEGERI 1 KOTA BENGKULU - Marita, Zadam; Saferi Wijaya, Andra; Septiyanti, Septiyanti; Rahma, Annisa; Susanti, Nia (Poltekkes Kemenkes Bengkulu, 2023)
Adolescence is a period of growth and development, both physically, mentally, and activity so that the need for food containing nutrients becomes quite large. The increase in nutritional needs in adolescence is related to the growth spurt, where nutrients that enter the body are used to increase body weight and height accompanied by an increase in the number and size of body cell tissue. Adolescents are one of the largest components in Indonesia. Therefore, adolescents must be able to make achievements in all fields so that they become the next generation of a quality nation. Symptoms of anemia are fatigue, dizziness, fatigue, weakness, shortness of breath, tingling, and feeling nauseous. Reduced amounts of hemoglobin in the blood in adolescents can have an impact on decreasing work productivity or reducing the ability to concentrate well so that it will reduce learning achievement. One of the causes of failure of studies in school is anemia. This situation arises because adolescents generally pay less attention to the quality of food. Most teenagers choose food based on taste considerations, not on nutritional considerations. Community service has been carried out on 36 female students at SMA Negeri 1 Kota Bengkulu. On Thursday, July 27, 2023, at Mushollah SMA 1 Kota Bengkulu at 08.00 WIB. The media used are leaflets, powerpoints, laptops, and projectors. The result obtained is that the students can absorb well the information conveyed and are very enthusiastic about participating in this health counseling activity.